KNOWLEDGE-BASED HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR IN DELTA STATE CIVIL SERVICE ASABA - OKOLIE, UGO CHUKS; EGDON, Thomastina Nkechi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
The goals that guided this study focused on the distinctive role that a skilled workforce played in achieving governmental objectives. Similar to other state civil services in Nigeria, the Delta State Civil Service was established to carry out governmental directives. The Delta State Government has struggled with subpar policy implementation over the years. In light of this, this study investigated the impact of knowledge-based human resource management policies on organizational citizenship behaviour in the Delta State Civil Service Asaba, Nigeria. These policies include recruitment and selection based on knowledge, training and development based on knowledge, performance evaluation based on knowledge, and compensation based on knowledge. By using the systematic random sampling technique, questionnaires were distributed to employees at the Delta State Civil Service Commission in Asaba, the state capital, in order to meet the study's objectives. This study used a sample size of 153 respondents and a survey research design. With the help of SPSS software version 23.0, descriptive and inferential statistics were used to analyze the data collected. Out of the 153 questionnaires distributed to respondents, 129 were retrieved and analyzed, accounting for 84.3% of the total copies distributed. The findings demonstrate, among other things, that knowledge-based human resource management policies (recruitment and selection, training and development, performance evaluation, and compensation) have a significant positive impact on organizational citizenship behaviour in the Delta State Civil Service Asaba, Nigeria. The study comes to the conclusion that by enhancing organizational knowledge and encouraging knowledge creation, human resource management affects organizational citizenship behaviour. The study recommends among others that Delta State Civil Service should make sure that its knowledge-based human resource management policies are such that support employees' civic behaviour and are capable of inspiring and retaining qualified workers for improved performance.